Reporte de caso: Recién nacido con asociación VACTERL y traqueomalacia: Case report: Newborn with VACTERL association and tracheomalacia - Huamán-Rodríguez, Martina (2022)
VACTERL association is the non-random co-occurrence of vertebral, anorectal, cardiac, tracheoesophageal, renal and limb congenital malformations, and in addition may be associated with tracheomalacia. The aim of this report is to describe the presence of congenital malformations in a case of VACTERL and tracheomalacia association. We report the case of a newborn whose adolescent mother reported occasional alcohol consumption. At birth he received CPR with orotracheal intubation and was diagnosed with VACTERL association and sepsis, which was treated with antibiotics. Since birth he presented stridor and at one month of life, the diagnosis of tracheomalacia was confirmed by laryngoscopy. We conclude that VACTERL association in a newborn may be accompanied by some other malformation, such as tracheomalacia, and its detection is essential for proper management and prevention of complications.